ANALISIS KELAYAKAN FINANSIAL USAHA TERNAK SAPI PERAH GISTING DAIRY FARM DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Dirasta, Suny; Affandi, Muhammad Irfan; Saleh, Yuliana (Lampung University, 2024)
Thisl researchl aims tol analyzel thel feasibility of dairy cattle business by employing investment assessment criterial NPV, lIRR, net lB/C, grossl B/C, payback period andl sensitivity. . Thisl research wasl conducted at Gisting Dairly Farm, Gisting District, Tanggamus Regency. Data collection was conducted from July toAugust 2022. Respondentsl for the research were l the ownerl and l employees ofl Gisting Dairyl Farm. The datal were analyzedl quantitativelyl by using measurementl criteria ofl financiall viability andl sensitivityl lanalyzes. The resultsl showedl thatl dairy cattlel businessl isl financially viablel asl indicatedl by NPVl valuesl ofl IDR 2,116,549,122.00; Net lB/C valuesl of 3.54; Grossl B/C valuesl of 1.54; IRRl values ofl 27.57 percent; PPl of 5.03 froml the economicl life ofl dairy cattlel for eightl years, andl dairy cattlel business isl still viablel despite of decreasing ofl milk sales cost byl 12 percent, andl increasing ofl cow maintenancel cost ofl 10 lpercent. lKey words: dairy cattle, lfeasibility, financial, sensitivity